Ripple mediated surface enhanced Raman spectroscopy on graphene. (February 2020) - Prasad, Alisha; Chaichi, Ardalan; Mahigir, Amirreza; Sahu, Sushant P.; Ganta, Deepak; Veronis, Georgios; Gartia, Manas Ranjan
Abstract: Surface-enhanced Raman spectroscopy (SERS) has single molecule level bio-chemical detection capabilities. Single layer graphene on SERS substrates shows modest enhancement factor (EF) (∼10) primarily from chemical enhancement (CE) mechanism. Improvement in EF will have significant impact on applications of graphene in optoelectronics. This limitation is caused by poor interaction of visible light at near infrared frequencies with graphene monolayers. We report an assembly of single-layer graphene (SLG) on a three-dimensional (3D) Au@Ag, core-shell structure that enhances light-matter interactions and modulates light absorption in graphene due to formation of graphene ripples. We demonstrate a SERS EF of ∼1, 000 using 633 nm excitation laser with the designed SLG/SERS substrate. The Raman scattering cross-section of R6G molecule was found to be enhanced by a factor of ∼10 2 –10 3, and limit of detection obtained was 100 pM using the SERS substrate. The enhancement is primarily due to increase in polarizability and anisotropy from rippled graphene substrate. The finite-difference-time-domain electromagnetic simulation showed enhancement of local electromagnetic field leading to enhanced excitation of the molecule. Density functional theory based quantum mechanical simulation studies showed the charge transfer from graphene-to-R6G molecule, leading to enhanced emission of Raman scattering. Graphical abstract: Image 1